Reversible Cerebral Vasoconstriction Syndrome: An Important Cause of Acute Severe Headache - Li Huey Tan; Oliver Flower (Emergency Medicine International)
Reversible cerebral vasoconstriction syndrome (RCVS) is an increasingly recognized and important cause of acute headache. The majority of these patients develop potentially serious neurological complications. Rigorous investigation is required to exclude other significant differential diagnoses. Differentiating RCVS from subarachnoid haemorrhage (SAH) and primary angiitis of the central nervous system (PACNS) may be difficult but has important therapeutic implications. This paper describes what is currently known about the epidemiology, pathophysiology, clinical, and diagnostic features of the syndrome, an approach to investigation, a summary of treatments, and what is known of prognosis.